Shelf life characteristics of bread produced from ozonated wheat flour. Issue 5 (20th December 2017) - Obadi, Mohammed; Zhu, Ke‐Xue; Peng, Wei; Sulieman, Abdellatif A.; Mahdi, Amer Ali; Mohammed, Khalid; Zhou, Hui‐Ming
Abstract: The objective of this work was to study the effect of ozone treatment on the quality of bread and its shelf life. Flour was treated with ozone gas a rate of 5 L/min for 5, 15, 25, 35, and 45 min. Baking studies showed that bread made from flour treated with ozone for 15 min exhibited improved quality properties (in terms of specific volume, bread color, and crumb cell numbers). Exposure to ozone for shorter times did not cause obvious changes in the major volatile compounds of bread. A shelf life tests showed that ozone gas treatment influenced the extent of starch crystallinity. The relative starch crystallinity of bread made from flour treated with ozone for 15 min was lower than the control value, as were the hardness, springiness, and cohesiveness. Microscopic examination of crumb structure revealed remarkable differences between control and treated breads. Practical applications: Although ozone is a naturally occurring substance found in the atmosphere, ozone can also be produced synthetically. Recently, ozone has come to be regarded as a new treatment for flour. Especially in countries where the chlorination is forbidden, ozone treatment may be of a great interest if it were associated with significant and reliable changes in flour. Ozone treatment of wheat flour tends to improve bread shelf life and quality in terms of physiochemical, baking properties, X‐ray diffraction data, volatile compound levels, crumb structure, and textural characteristics. Given such findings, desirable shelf life and bread qualities may be achieved when ozone is used as a flour oxidant prior to bread baking. Analyses of the effects of ozone gas on treatment of flour on bread shelf life and quality would aid the production of high quality and extend the shelf life of bread.